2022
DOI: 10.1001/jamanetworkopen.2022.27126
|View full text |Cite|
|
Sign up to set email alerts
|

Factors Associated With Declining Lung Cancer Screening After Discussion With a Clinician in a Cohort of US Veterans

Abstract: ImportanceLung cancer screening (LCS) is underused in the US, particularly in underserved populations, and little is known about factors associated with declining LCS. Guidelines call for shared decision-making when LCS is offered to ensure informed, patient-centered decisions.ObjectiveTo assess how frequently veterans decline LCS and examine factors associated with declining LCS.Design, Setting, and ParticipantsThis retrospective cohort study included LCS-eligible US veterans who were offered LCS between Janu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 54 publications
0
7
0
Order By: Relevance
“…Identified barriers hampering LCS participation include travel issues or psychological factors (anxiety and stigma), which negatively impact a person’s motivation to attend [ 25 , 26 ]. Uptake and adherence disparities were potentially related to structural barriers preventing receipt of equitable care, lower socioeconomic status and difficulties in obtaining reimbursements [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…Identified barriers hampering LCS participation include travel issues or psychological factors (anxiety and stigma), which negatively impact a person’s motivation to attend [ 25 , 26 ]. Uptake and adherence disparities were potentially related to structural barriers preventing receipt of equitable care, lower socioeconomic status and difficulties in obtaining reimbursements [ 27 29 ].…”
Section: Discussionmentioning
confidence: 99%
“…The BRFSS survey question assessing LCS use does not differentiate between initial LDCT and subsequent scans, and different steps along the process of LCS may be associated with different barriers for patients. 20 , 53 Furthermore, the answer choices for self-rated health in the BRFSS (excellent/very good/good/fair/poor) differ somewhat from those used by NELSON investigators because they excluded individuals with moderate or bad self-rated health, and the question that ascertained difficulty in climbing stairs also asked about difficulty in walking in general.…”
Section: Discussionmentioning
confidence: 99%
“…Previous analyses in the Veterans Health Administration (VHA), 17 which serves approximately 49% of veterans, 18 , 19 have shown increased acceptance of screening among Black and Hispanic veterans after being offered LCS but also increased risk of delayed or no follow-up after initial LDCT scans among Black veterans. 20 …”
Section: Introductionmentioning
confidence: 99%
“…Strategies recommended to overcome these barriers include providing training to all practice staff, identifying a staff member to champion this service, and having clear roles about who is responsible for ordering supplies and applying fluoride varnish . Additionally, prior research on preventive services has found that clinician recommendation is one of the strongest predictors of patient receipt of these services in adult populations . This has also been shown in pediatric populations, especially related to routine vaccines.…”
Section: Discussionmentioning
confidence: 99%